The influence of women's political and economic participation on gender empowerment measure in matrilineal communities in West Sumatera / Beta Santria Sholehah and Dasman Lanin - Sholehah, Beta Santria; Lanin, Dasman (2021)
The conception and movement of gender equality as intensified in the 5th agenda of the Sustainable Development Goals is a form of attention to the acquisition and protection of equal rights for men and women to be able to participate in various development sectors as subjects (agents of change) to suppress the level of discrimination and inequality and improve welfare. However, the achievements of women's participation in the political or economic in West Sumatra are still very low. This can be viewed from the women's income distribution contributions in 2020 in West Sumatra which was only 37.57%. In politics, the involvement of women in the legislature is also only 4.62%. This figure shows the lowest level of women's participation in West Sumatra in the last 10 years. Considering the affirmative policy provisions, namely Law No. 10 of 2008 concerning General Elections for Legislative Members and Law No. 2 of 2011 concerning Political Parties, it proclaimed that the quota for women's involvement in politics is at least 30%. Evaluation of accomplishes increase in gender equality measured through the Gender Empowerment Measure (GEM). Based on GEM's achievements in 2020, West Sumatra was ranked 32nd out of 34 provinces in Indonesia with a score of 58.28, additionally have a high level of disparity between districts and cities. When viewed from a cultural perspective, West Sumatra is one of the provinces in Indonesia where the majority of the population are Minangnese that adhere to the matrilineal system. Normatively, the matrilineal system that is applied regulates the issue of lineage taken from the woman's/mother's side. Therefore, the son or daughter will inherit their mother's tribe. The dissemination of economic resources such as occupancy of land, inheritance, utilize of fields along with the results is also held or managed by the mother (Hakimi, 2001). Political activity by women has also been proacting for a long time in Minangkabau society (Verayanti, et al., 2003). The low participation of women shows that gender inequality also occurs in matrilineal society in West Sumatra. Therefore, this study aims to determine how much influence women's political and economic participation (represented by women's involvement in parliament and women's income contribution) in the matrilineal society of West Sumatra to the Gender Empowerment Measure?